La educación sexual y el embarazo adolescente. Análisis de la política pública desde un enfoque de género (2021)
Despite public health and education efforts, adolescent pregnancy remains latent in Colombia, especially in the rural population. Therefore, this article analyzes the National Policy on Sexuality, Sexual Rights and Reproductive Rights and specifically the sexual education strategy implemented by the municipality of úmbita, Boyacá. This analysis is made from two related theoretical perspectives: gender and comprehensive sexuality education. The foregoing using the case study method and the semi-structured interview technique with adolescents and policy operators. It is concluded that although the policy is framed within a comprehensive approach, its implementation continues framed in traditionalist approaches due to cultural obstacles such as religion and romantic love, and to gender inequities that limit the experience of the sexuality of women and reduces it to the reproduction and deserotized sexual act.